Flexible substrate material doped with two-dimensional material and preparation method of sensor of flexible substrate material

By optimizing two-dimensional material electrodes through composite doping and high-precision integration processes, the problems of sensor resolution and stability are solved, and high-sensitivity multi-physical quantity detection is achieved, which is suitable for smart equipment and medical health fields.

CN120793914AActive Publication Date: 2025-10-17GUANGZHOU AOSONG ELECTRONIC CO LTD

Patent Information

Application Number
CN202510872445.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-26
Publication Date
2025-10-17
Estimated Expiration
2045-06-26

AI Technical Summary

Technical Problem

Existing two-dimensional material sensors have difficulty achieving high resolution and precise detection of multiple physical quantities due to poor uniformity of single element doping and significant interlayer coupling effects. In addition, traditional preparation processes have low alignment accuracy and many interface defects, which affect device performance.

Method used

A composite doping system is adopted to form a uniformly distributed dual-doping defect structure on the surface of the two-dimensional material and at the grain boundary defects through atomic layer deposition of nitrogen and boron. Combined with the insulating isolation layer and gradient doping heterojunction design, combined with H2 plasma treatment and self-aligned lithography technology, high-precision integration is achieved.

Benefits of technology

The response sensitivity and signal-to-noise ratio of two-dimensional material electrodes have been significantly improved, signal loss has been reduced, the resolution and stability of the sensor have been improved, and the environmental adaptability and mechanical stability of the device have been enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120793914A_ABST
    Figure CN120793914A_ABST
Patent Text Reader

Abstract

The invention discloses a flexible substrate material doped with a two-dimensional material and a preparation method of a sensor of the flexible substrate material, and belongs to the technical field of array sensors. The electrode material comprises a two-dimensional material substrate, a composite doping atom layer and an insulation isolation layer, high-density defect sites are formed through H2 plasma processing, uniform distribution of doping atoms is achieved in combination with atomic layer deposition, and an electrode and a temperature-sensitive layer are precisely integrated through the self-alignment photoetching technology. According to the scheme, the electronic structure of the two-dimensional material is optimized through the composite doping synergistic effect, the multi-layer heterojunction design and the high-precision preparation process are combined, the response capacity of the electrode to weak pressure signals is remarkably improved, and high resolution and stability of the sensor in pressure and temperature detection are achieved. The method has a wide application prospect in the fields of wearable equipment, medical monitoring, robot tactile perception and the like.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of electronic materials, in particular to a flexible substrate material doped with two-dimensional material and a preparation method of a sensor thereof. BACKGROUND

[0002] In the field of arrayed sensors, the performance of electrode materials directly affects the ability of sensors to capture weak signals and resolution. Traditional electrode materials such as metal thin films or carbon-based composites have problems such as low electron transport efficiency and insufficient surface active sites, which are difficult to meet the demand of high sensitivity pressure detection. Two-dimensional materials such as graphene and molybdenum disulfide have become ideal choices for electrode materials due to their excellent electrical properties, large specific surface area and atomic thickness, but their intrinsic electronic structure limits the response ability to pressure signals. In the prior art, although single-element doping can improve the performance of two-dimensional materials, the problems of poor doping uniformity and significant interlayer coupling effect limit the improvement of sensor resolution, and the lack of collaborative design with temperature-sensitive layers and insulating layers makes it difficult to achieve accurate detection of multiple physical quantities. In addition, traditional preparation processes have low alignment accuracy and many interface defects when integrating electrodes and sensor functional layers, which further affects the performance of the device. Therefore, there is an urgent need for a technical solution that optimizes the electronic structure of two-dimensional materials through a composite doping system and combines a high-precision integration process to break through the bottleneck of existing sensors in resolution and stability. SUMMARY

[0003] To solve the technical problem in the prior art that although single-element doping can improve the performance of two-dimensional materials, the problems of poor doping uniformity and significant interlayer coupling effect limit the improvement of sensor resolution, and the lack of collaborative design with temperature-sensitive layers and insulating layers makes it difficult to achieve accurate detection of multiple physical quantities, the present application provides a flexible substrate material doped with two-dimensional material and a preparation method of a sensor thereof.

[0004] In a first aspect, the present application provides a flexible substrate material doped with two-dimensional material, comprising: a two-dimensional material substrate, the two-dimensional material being at least one of graphene, molybdenum disulfide, tungsten diselenide or black phosphorus; a composite doping atom layer, the composite doping atom comprising nitrogen and boron, the atomic doping ratio of nitrogen to boron being 1:3 to 3:1, the composite doping atom being uniformly distributed on the surface and grain boundary defects of the two-dimensional material substrate; an insulating isolation layer, the insulating isolation layer being boron nitride nanosheet or aluminum oxide film, covering the surface of the two-dimensional material substrate, and having a thickness of 5-20 nm.

[0005] In one embodiment, the two-dimensional material substrate is a heterojunction formed by graphene and MoS2, the graphene layer in the heterojunction has a thickness of 1-3 atomic layers, the MoS2 layer has a thickness of 2-5 atomic layers, and the composite doping atom preferentially enriches at the edge active sites of the MoS2 layer.

[0006] In one embodiment, the total doping concentration of the composite doped atoms is 1 x 10 13 cm -2 to 5 x 10 14 cm -2 , and the surface work function of the two-dimensional material substrate is 4.2-5.1 eV, which is continuously adjustable by adjusting the doping ratio of nitrogen and boron.

[0007] In a second aspect, the application also provides a preparation method of a high-resolution arrayed sensor based on any of the electrode materials, comprising the following steps: two-dimensional material flexible substrate pretreatment: transferring a two-dimensional material thin film to a silicon or polyimide substrate, and using H2 plasma treatment, with the treatment parameters being: H2 flow rate 60-120 mL / min, radio frequency power 1.4-1.8 A, and treatment time 3-10 minutes; composite doping process: sequentially introducing NH3 and B2H6 gas, with a flow rate ratio of 1:1 to 3:1, and performing atomic layer deposition at 200-400°C, with a deposition cycle of 50-200 times; insulating isolation layer preparation: forming a BN nanosheet layer or an Al2O3 film on the surface of the doped two-dimensional material by spin coating or chemical vapor deposition, with a thickness controlled by deposition time of 5-20 nm; using a self-aligned photolithography technology to define an arrayed electrode pattern on the surface of the flexible substrate material, with a line width ≤10 μm, and depositing a vanadium oxide temperature-sensitive layer by electron beam evaporation, with a thickness of 100-300 nm, and connecting to a signal processing ASIC chip through a conductive via with a diameter ≤5 μm.

[0008] In one embodiment, the purity of the NH3 gas is ≥99.999%, the partial pressure of the B2H6 gas is controlled to be 1-5 Pa, and the substrate temperature fluctuation during the deposition process is ≤±5°C.

[0009] In one embodiment, when the two-dimensional material substrate is a graphene / MoS2 heterojunction, the H2 plasma treatment in step forms sulfur vacancy defects on the surface of the MoS2 layer, with a defect density of 1 x 10 12 cm -2 to 5 x 10 12 cm -2 .

[0010] In one embodiment, the overlay accuracy of the self-aligned photolithography technology in step is ≤2 μm, a deep ultraviolet photolithography light source is used, with a wavelength of 248 nm, and the edge alignment error between the electrode and the temperature-sensitive layer is ≤1 μm. In one embodiment, the signal processing ASIC chip integrates a low-noise amplifier and a 24-bit delta-sigma A / D converter, the aspect ratio of the conductive via is 5:1 to 10:1, and copper or gold is used for filling.

[0011] In one of the embodiments, a gradient-doped heterostructure is further included, which is formed between the two-dimensional material substrate and the insulating isolation layer by segmentally controlling the ALD gas flow, with N-doping concentration gradient of 10%-90% and B-doping concentration gradient of 90%-10%, and the band offset ΔE of the gradient heterojunction is 0.3-0.8 eV.

[0012] In one of the embodiments, the arrayed electrode units of the sensor are distributed in an m x n matrix, with m, n≥2, the size of a single electrode unit is 20 μm x 20 μm to 50 μm x 50 μm, the unit spacing is 50 μm to 100 μm, adjacent electrode units are isolated by a silicon dioxide insulating layer, and the thickness of the insulating layer is 1-5 μm.

[0013] Further, when the two-dimensional material substrate is black phosphorus, the composite doping atoms further include sulfur, forming an N-B-S ternary doping system, and the atomic doping ratio of S is N:B:S = 1:1:1 to 1:3:1. The sensor further includes a flexible encapsulation layer, the encapsulation layer material is polydimethylsiloxane or epoxy resin, and the thickness is 50-200 μm, the surface of the encapsulation layer is provided with a microstructure protrusion, the height is 50-100 μm, and the pitch is 200-500 μm. When the two-dimensional material substrate is tungsten diselenide, the doping depth of the composite doping atoms is 5-20 nm, and the defect density is controlled by adjusting the H2 plasma treatment time. When the Al2O3 thin film is prepared by chemical vapor deposition, the reaction gas is trimethylaluminum and deionized water, the deposition temperature is 150-250 °C, and the deposition rate is 0.1-0.5 nm / cycle. The crystalline orientation of the vanadium oxide temperature-sensitive layer is a crystal face, and the preferred growth is achieved by controlling the annealing temperature of 400-600 °C and the time of 30-90 minutes.

[0014] The application significantly improves the performance of two-dimensional material electrodes and sensors through the synergistic optimization of composite doping system and multi-layer structure design. In terms of electrode materials, the composite doping of nitrogen and boron forms a double-doped defect structure on the surface and grain boundary defects of two-dimensional materials. Compared with single doping, it effectively regulates the electronic structure and surface active site distribution of the material, enhances the carrier migration ability induced by pressure signals, and thus improves the response sensitivity of the electrode to weak pressure changes. The introduction of an insulating isolation layer reduces interlayer electrical interference, combined with the band offset design of the gradient-doped heterojunction, forming an efficient charge transport path, reducing signal loss and improving signal-to-noise ratio. In terms of preparation process, the combination of H2 plasma pretreatment and atomic layer deposition realizes the atomic-level uniform distribution of doped atoms, overcoming the problem of uneven diffusion in traditional doping process, ensuring the consistency of material performance; the precise integration of self-aligned lithography technology and conductive vias reduces the alignment error of the electrode and the temperature-sensitive layer, reduces the parasitic capacitance and improves the signal transmission efficiency. The arrayed electrode unit design of the sensor combined with the flexible packaging layer not only improves the spatial resolution, but also enhances the environmental adaptability and mechanical stability of the device. The overall scheme breaks through the limitations of existing two-dimensional material sensors in resolution, stability and integration accuracy through the deep integration of material modification, structural innovation and process optimization, providing an efficient solution for multi-physical quantity accurate detection in complex scenarios, and has significant application value and technical advantage in intelligent equipment, medical health and other fields. BRIEF DESCRIPTION OF DRAWINGS

[0015] Figure 1 is a flexible substrate material section structure schematic diagram provided by an embodiment of the application;

[0016] Figure 2 is a working step diagram of a preparation method provided by an embodiment of the application. DETAILED DESCRIPTION

[0017] In order to make the purpose, technical scheme and advantages of the present application clearer, the specific embodiments of the present application will be further described in detail below in combination with the drawings. It can be understood that the specific embodiments described herein are only used to explain the present application, but not to limit the present application. In addition, it should be noted that, in order to facilitate description, only parts related to the present application are shown in the drawings, but not all contents. Before discussing the example embodiments in more detail, it should be mentioned that some example embodiments are described as processes or methods depicted as flowcharts. Although the flowchart describes each operation (or step) as a sequential process, many of the operations can be implemented in parallel, concurrently or simultaneously. In addition, the order of the operations can be rearranged. The process can be terminated when its operations are completed, but can also have additional steps not included in the drawings. The process can correspond to a method, function, procedure, subroutine, subprogram, etc.

[0018] The terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not used to describe a specific order or sequence. It should be understood that the data thus used can be interchanged under appropriate circumstances, so that the embodiments of the present application can be implemented in an order other than that illustrated or described herein, and the objects distinguished by "first", "second", etc. are generally of a kind and do not limit the number of objects, for example, the first object can be one or more. In addition, "and / or" in the specification and claims indicates at least one of the connected objects, and the character " / ", generally indicates that the front and rear associated objects are in a "or" relationship.

[0019] In the field of arrayed sensors, the performance of electrode materials directly affects the ability of sensors to capture weak signals and resolution. Traditional electrode materials such as metal thin films or carbon-based composite materials have problems such as low electron transport efficiency and insufficient surface active sites, making it difficult to meet the demand for high sensitivity pressure detection. Two-dimensional materials such as graphene and molybdenum disulfide have become ideal choices for electrode materials due to their excellent electrical properties, large specific surface area and atomic-level thickness, but their intrinsic electronic structure limits their response ability to pressure signals. In the prior art, single-element doping can improve the performance of two-dimensional materials, but the problems of poor doping uniformity and significant interlayer coupling effect limit the improvement of sensor resolution, and the lack of collaborative design with temperature-sensitive layers and insulating layers makes it difficult to achieve accurate detection of multiple physical quantities. In addition, traditional preparation processes have low alignment accuracy and many interface defects when integrating electrodes and sensor functional layers, further affecting device performance. Therefore, there is an urgent need for a technical solution that optimizes the electronic structure of two-dimensional materials through a composite doping system and combines a high-precision integration process to break through the bottleneck of existing sensors in resolution and stability.

[0020] Therefore, the present application discloses a flexible substrate material doped with two-dimensional materials and a preparation method of a sensor thereof, which belongs to the technical field of arrayed sensors. The electrode material includes a two-dimensional material substrate, a composite doping atomic layer, and an insulating isolation layer. High-density defect sites are formed by H2 plasma treatment, uniform distribution of doping atoms is achieved by atomic layer deposition, and self-aligned photolithography technology is used to precisely integrate electrodes and temperature-sensitive layers. This solution optimizes the electronic structure of two-dimensional materials through the synergistic effect of composite doping, combines multi-layer heterojunction design and high-precision preparation process, significantly improves the response ability of electrodes to weak pressure signals, and realizes high resolution and stability of sensors in pressure and temperature detection. The present application has wide application prospects in the fields of wearable devices, medical monitoring, robot tactile perception, etc.

[0021] The present embodiment details the preparation method of a flexible substrate material doped with two-dimensional materials and a sensor thereof to realize the technical solution described in the claims.

[0022] Embodiment 1

[0023] Reference Figure 1 The flexible base material of the doped two-dimensional material includes:

[0024] 101. An insulating isolation layer covering the entire surface of the two-dimensional material base and the composite doping atom layer (corresponding to the uppermost area of the section). It is prepared by using boron nitride nanosheet and / or aluminum oxide film, and the thickness is precisely controlled at 5-20 nm, which plays a role of "insulating barrier" to avoid unnecessary electrical interference between the electrode and the external circuit / matrix.

[0025] 102. A composite doping atom layer attached to the surface of the two-dimensional material base and simultaneously penetrating and filling the grain boundary defects inside the base (i.e. the microscopic gaps and defects of the base are covered by doping atoms). It is composed of nitrogen (N) and boron (B) atoms, and the atomic doping ratio of the two is strictly controlled between 1:3 and 3:1, realizing atomic-level composite modification and optimizing the electrical properties of the electrode.

[0026] 103. A two-dimensional material base, the basic support layer of the structure, which uses at least one two-dimensional material among graphene, molybdenum disulfide, tungsten diselenide, and black phosphorus to construct the skeleton of the electrode by taking advantage of its ultra-thin and high-conductive properties.

[0027] The electrode material takes two-dimensional material as the base, including at least one of graphene, molybdenum disulfide (MoS2), tungsten diselenide (WSe2), or black phosphorus (BP), and forms a defect regulation structure through the composite doping of nitrogen (N) and boron (B). Taking the graphene / MoS2 heterojunction electrode as an example, the bottom layer is 1-3 atomic layers thick of graphene, providing a high-speed electron transmission channel, and the upper layer is 2-5 atomic layers thick of MoS2, which utilizes its edge active sites to achieve preferential enrichment of doping atoms. The composite doping atoms are uniformly distributed on the surface and grain boundary defects of the two-dimensional material at an atomic ratio of 1:3 to 3:1, and atomic-level uniform doping is achieved through atomic layer deposition (ALD) technology, forming a double-doped defect structure that significantly improves the surface activity and electron transmission efficiency of the material. The insulating isolation layer uses 5-20 nm thick boron nitride (BN) nanosheet or aluminum oxide (Al2O3) film, which is combined with the two-dimensional material base through van der Waals force or covalent bond, inhibiting interlayer electrical interference and protecting the electrode structure.

[0028] A two-dimensional material film (such as graphene, MoS2 heterojunction) is transferred onto a silicon (Si), polyimide (PI) or other substrate by wet transfer or direct growth, and a high-density defect site is constructed by H2 plasma treatment. For example, a graphene / MoS2 heterojunction on a silicon substrate, with an H2 flow rate controlled at 60-120 mL / min, a radio frequency power of 1.4-1.8 A, and a treatment time of 3-10 minutes, forms sulfur (S) vacancy defects on the surface of the MoS2 layer, with a defect density of 1×10 12 cm -2 to 5×10 12 cm -2 , providing anchoring sites for subsequent doping atoms. This treatment process precisely controls the defect density and distribution by adjusting plasma parameters, ensuring uniform adsorption of doping atoms. In an ALD device, NH3 and B2H6 gases are sequentially introduced, with a flow ratio of 1:1 to 3:1, and atomic layer deposition is performed at 200-400°C, with a deposition cycle of 50-200 times, to achieve simultaneous doping of nitrogen and boron atoms. For example, a black phosphorus-based electrode is introduced to form an N-B-S ternary doping system, and by controlling the gas flow in stages, a gradient-doped heterojunction is constructed between the two-dimensional material substrate and the insulating isolation layer: the bottom layer N-doping concentration gradually increases from 10% to 90%, and the top layer B-doping concentration correspondingly decreases from 90% to 10%, forming an energy band offset (ΔE) of 0.3-0.8 eV, promoting the directional migration of carriers and signal separation. During the doping process, the purity of NH3 gas is ≥99.999%, the partial pressure of B2H6 gas is controlled at 1-5 Pa, and the substrate temperature fluctuation is ≤±5°C, ensuring that the doping uniformity error is ≤±5%.

[0029] An arrayed electrode pattern is defined using a self-aligned lithography technique, with a line width ≤10 μm and a overlay accuracy ≤2 μm. Precise alignment of the electrode and temperature-sensitive layer (such as vanadium oxide VO2) is achieved through deep ultraviolet (DUV) lithography light source (wavelength 248 nm), with an edge alignment error ≤1 μm. For example, a vanadium oxide temperature-sensitive layer is prepared, and a 100-300 nm thick film is deposited on the electrode surface by electron beam evaporation or pulsed laser deposition technology, and annealed at 400-600°C to achieve (110) crystal face preferential growth, improving temperature response sensitivity. Conductive vias are filled with copper (Cu) or gold (Au) with a diameter ≤5 μm, with a depth-to-width ratio of 5:1 to 10:1, and a contact resistance ≤100 mΩ, ensuring low-noise connection with the signal processing ASIC chip.

[0030] The sensor surface is covered with a flexible encapsulation layer (such as polydimethylsiloxane PDMS or epoxy resin) with a thickness of 50-200 pm. The surface is prepared with microstructured protrusions with a height of 50-100 pm and a pitch of 200-500 pm by micro-molding techniques to enhance the pressure transfer efficiency. For high-humidity environment applications, the encapsulation layer surface is coated with a nanoscale moisture barrier (such as polytetrafluoroethylene PTFE) with a water vapor permeation rate of less than 5 x 10-13 g / (cm 2 ·s), and a humidity compensation electrode is integrated to correct the environmental interference in real time through differential detection, ensuring the stability of the sensor in complex environments.

[0031] In some embodiments, during the preparation process, graphene is first selected as the two-dimensional material substrate for composite doping. The two-dimensional material graphene substrate is treated by hydrogen plasma. During the treatment process, the gas flow rate is controlled at 60 to 120 mL / min, and the radio frequency power is set to 1.4 to 1.8 A, so as to ensure that the active sites on the surface of the graphene are fully exposed. After this pretreatment, the surface of the two-dimensional material substrate has appropriate surface energy, which facilitates subsequent doping. Atomic layer deposition (ALD) doping is performed using nitrogen and boron gases. In this step, the flow ratio of nitrogen and boron gases is controlled at 1:1 to 3:1, and the gas flow is deposited at a temperature of 200 to 400°C. The period of each deposition is 50 to 200 times to ensure the uniformity and layer structure of the doping. After this process, the doped atoms of nitrogen and boron are preferentially distributed on the surface of the graphene and at the grain boundary defects, with a doping ratio of 1:3 to 3:1, and finally a composite doped electrode material with high efficient conductivity and good stability is obtained. Subsequently, a nanosheet layer is formed on the surface of the two-dimensional material by spin coating, or an aluminum oxide (Al2O3) film is deposited on the surface of the material by chemical vapor deposition (CVD) method, and the thickness of the insulating isolation layer is controlled at 5 to 20 nm to improve the stability and signal transmission effect of the sensor. The array preparation of the sensor adopts a self-alignment photolithography technology. First, the array electrode pattern is defined on the surface of the electrode material, ensuring that the line width of the pattern is not more than 10 pm, and a vanadium oxide temperature-sensitive layer is deposited by electron beam evaporation, with a layer thickness of 100 to 300 nm. The role of the temperature-sensitive layer is to enhance the response of the sensor signal to temperature, further improving its resolution. Then, the electrode is connected with a signal processing chip (ASIC) through a conductive via with a diameter of not more than 5 pm, ensuring the efficiency and accuracy of the signal transmission process. Finally, the array electrode units of the sensor are distributed in an m x n matrix, and the size of a single electrode unit is 20 pm x 20 pm to 50 pm x 50 pm. Adjacent units are isolated by a silicon dioxide insulating layer with a thickness of 1 to 5 pm. Through such a design, we can realize a higher resolution sensor array suitable for fine detection and various sensing applications.

[0032] The embodiment introduces a preparation method of a two-dimensional material electrode with gradient doping, and further discusses its application in high-resolution arrayed sensors.

[0033] Reference Figure 2 In a second aspect, the present application also provides a preparation method of a high-resolution arrayed sensor based on any of the electrode materials, including the following steps: two-dimensional material flexible substrate pretreatment: transferring a two-dimensional material thin film to a silicon or polyimide substrate, and treating with H2 plasma, with the treatment parameters being: H2 flow rate 60-120 mL / min, radio frequency power 1.4-1.8 A, and treatment time 3-10 minutes; composite doping process: sequentially introducing NH3 and B2H6 gases with a flow ratio of 1:1 to 3:1, and performing atomic layer deposition (ALD) at 200-400℃, with a deposition cycle of 50-200 times; insulating isolation layer preparation: forming BN nanosheet layers or Al2O3 films on the surface of the doped two-dimensional material by spin coating or chemical vapor deposition, with a thickness controlled by deposition time of 5-20 nm; using a self-aligned photolithography technology to define arrayed electrode patterns on the surface of the flexible substrate material, with a line width ≤10 μm, and depositing a vanadium oxide temperature-sensitive layer by electron beam evaporation, with a thickness of 100-300 nm, and connecting to a signal processing ASIC chip through a conductive via with a diameter ≤5 μm.

[0034] This method ensures the performance and stability of the sensor through a series of process steps. First, in the pretreatment stage of the two-dimensional material substrate, the two-dimensional material thin film is transferred to a silicon or polyimide substrate and treated with H2 plasma, with the treatment parameters controlled as follows: H2 flow rate in the range of 60 to 120 mL / min, radio frequency power set to 1.4 to 1.8 A, and treatment time controlled between 3 to 10 minutes, to ensure that the chemical activity of the two-dimensional material surface is suitable for subsequent processes. Then, in the composite doping process, ammonia (NH3) and diborane (B2H6) gases are sequentially introduced with a flow ratio controlled between 1:1 and 3:1, and atomic layer deposition (ALD) is performed at a temperature of 200 to 400℃, with a deposition cycle set between 50 to 200 times, to ensure uniform distribution of the doping elements and optimize the electronic properties of the material.

[0035] In the preparation stage of the insulating isolation layer, a layer of BN nanosheet or Al2O3 film is formed on the surface of the doped two-dimensional material by spin coating or chemical vapor deposition (CVD) technology. The thickness of the film is controlled between 5 to 20 nm by deposition time to achieve good electrical insulation. Subsequently, a self-aligned photolithography technique is used to define the arrayed electrode pattern, with the electrode line width controlled within 10 μm, high precision requirements, and overlay error not exceeding 2 μm. The light source is deep ultraviolet lithography (248 nm) to ensure high-precision pattern transfer. The alignment error between the electrode and the temperature-sensitive layer is required to be not more than 1 μm. During the electrode deposition process, a vanadium oxide (VOx) temperature-sensitive layer is deposited by electron beam evaporation technology, with the thickness of the temperature-sensitive layer controlled between 100 to 300 nm, and connected to the signal processing ASIC chip through a conductive via with a diameter not exceeding 5 μm to ensure efficient and low-noise signal transmission.

[0036] In certain embodiments, the purity of the ammonia gas (NH3) used is required to be ≥99.999%, and the partial pressure of the diborane gas (B2H6) is controlled to be 1 to 5 Pa. The substrate temperature fluctuation during deposition does not exceed ±5℃, thereby ensuring the high quality of the material. In particular, in the case of using graphene / MoS2 heterojunction, H2 plasma treatment forms sulfur vacancy defects on the surface of the MoS2 layer, with the defect density controlled between 1×10 12 cm -2 to 5×10 12 cm -2 , optimizing the electrical conductivity of the material and the response speed of the sensor.

[0037] In addition, the present application also relates to a manufacturing method of a gradient-doped heterostructure. By segmentally controlling the ALD gas flow between the two-dimensional material substrate and the insulating isolation layer, the N-doping concentration gradient is gradually increased from 10% to 90%, and the B-doping concentration gradient is gradually reduced from 90% to 10%. The energy band offset (ΔE) of the gradient heterojunction is controlled between 0.3 to 0.8 eV, thereby further enhancing the sensitivity and selectivity of the sensor.

[0038] In terms of signal processing unit, the sensor integrates a low-noise amplifier and a 24-bit delta-sigma A / D converter to ensure the accuracy and stability of signal processing. The aspect ratio of the conductive via is set between 5:1 to 10:1, and copper or gold is used for filling to ensure efficient and stable current transmission. Finally, the arrayed electrode unit of the sensor is distributed in an m×n matrix, where m, n ≥ 2. The size of a single electrode unit is controlled between 20 μm×20 μm to 50 μm×50 μm, the unit spacing is 50 μm to 100 μm, adjacent electrode units are isolated by a silicon dioxide insulating layer, and the thickness of the insulating layer is controlled between 1 to 5 μm to ensure the signal independence between electrodes and the clarity of transmission.

[0039] In one of the embodiments, the purity of the NH3 gas is ≥99.999%, the partial pressure of the B2H6 gas is controlled to be 1-5 Pa, and the substrate temperature fluctuation during the deposition process is ≤±5℃.

[0040] In one of the embodiments, when the two-dimensional material substrate is a graphene / MoS2 heterojunction, the step H2 plasma treatment forms sulfur vacancy defects on the surface of the MoS2 layer, and the defect density is 1×10 12 cm -2 to 5×10 12 cm -2 .

[0041] The overlay accuracy of the self-aligned photolithography technology in the step is ≤2μm, a deep ultraviolet photolithography light source is used, the wavelength is 248nm, and the edge alignment error between the electrode and the temperature-sensitive layer is ≤1μm. In one of the embodiments, the signal processing ASIC chip integrates a low-noise amplifier and a 24-bit delta-sigma A / D converter, the aspect ratio of the conductive via is 5:1 to 10:1, and copper or gold is used for filling.

[0042] In one of the embodiments, the gradient doped heterojunction building step further comprises: between the two-dimensional material substrate and the insulating isolation layer, by segmentally controlling the ALD gas flow, forming an N-doped concentration gradient of 10%-90% and a B-doped concentration gradient of 90%-10%, and the band offset ΔE of the gradient heterojunction is 0.3-0.8eV.

[0043] In one of the embodiments, the arrayed electrode unit of the sensor is in an m×n matrix distribution, m, n≥2, the size of a single electrode unit is 20μm×20μm to 50μm×50μm, the unit spacing is 50μm to 100μm, adjacent electrode units are isolated through a silicon dioxide insulating layer, and the thickness of the insulating layer is 1-5μm.

[0044] Further, when the two-dimensional material substrate is black phosphorus, the composite doping atoms further include sulfur, forming a N-B-S ternary doping system, and the atomic doping ratio of S is N:B:S = 1:1:1 to 1:3:1. The sensor further comprises a flexible encapsulation layer, the encapsulation layer material is polydimethylsiloxane or epoxy resin, the thickness is 50-200 μm, and the surface of the encapsulation layer is provided with a microstructure protrusion with a height of 50-100 μm and a pitch of 200-500 μm. When the two-dimensional material substrate is tungsten diselenide, the doping depth of the composite doping atoms is 5-20 nm, and the defect density is controlled by adjusting the H2 plasma treatment time. When the Al2O3 film is prepared by chemical vapor deposition, the reaction gas is trimethylaluminum and deionized water, the deposition temperature is 150-250 ℃, and the deposition rate is 0.1-0.5 nm / cycle. The crystalline orientation of the vanadium oxide temperature-sensitive layer is a crystal face, and the preferred growth is achieved by controlling the annealing temperature of 400-600 ℃ and the time of 30-90 minutes.

[0045] In this embodiment, graphene is selected as the two-dimensional material substrate, and a gradient doping structure of nitrogen and boron is formed by segmentally controlling the gas flow of atomic layer deposition (ALD). Specifically, the nitrogen doping concentration gradually increases from 10% to 90%, while the boron doping concentration gradually decreases from 90% to 10%. This gradient doping structure not only enhances the conductivity of the electrode, but also significantly improves the stability and response speed of the electrode.

[0046] To ensure the uniformity and gradient of the doping effect, the gas flow is precisely controlled during the doping process, the controlled gas flow ratio is 1:1 to 3:1, and the deposition temperature is ensured to be between 200 and 400 ℃. In this process, the doping ratio and distribution of nitrogen and boron are gradually realized by controlling the gas flow, thereby achieving good gradient doping effect. In order to enhance the stability of the electrode material, boron nitride nanosheets and aluminum oxide films are further deposited on the surface of the two-dimensional material as insulating isolation layers, and the thickness of the isolation layer is 5 to 20 nm. Then, the spin coating method and CVD technology are used to form nanosheet layers or Al2O3 films on the surface, which provides guarantee for the long-term stable operation of the sensor.

[0047] Through the above steps, a two-dimensional material electrode with good gradient doping structure is finally obtained in this embodiment, and it is successfully applied to the preparation of a high-resolution array sensor. The array design of the sensor adopts a self-aligned photolithography technology, and a vanadium oxide temperature-sensitive layer is deposited by electron beam evaporation, ensuring that the temperature response performance of the sensor reaches the expected target. By precisely controlling the size and pitch of the electrode pattern, we realize a higher resolution sensor array suitable for various high-precision detection tasks.

[0048] By the above technical solution, through the synergistic optimization of the composite doping system and the multi-layer structure design, the performance of the two-dimensional material electrode and the sensor is significantly improved. In terms of electrode material, the composite doping of nitrogen and boron forms a double-doped defect structure at the surface of the two-dimensional material and the grain boundary defects. Compared with single doping, the electronic structure and surface active site distribution of the material are effectively controlled, the carrier migration ability induced by the pressure signal is enhanced, and the response sensitivity of the electrode to weak pressure changes is improved. The introduction of the insulating isolation layer reduces the interlayer electrical interference, combined with the band offset design of the gradient doping heterojunction, forms an efficient charge transport path, reduces signal loss and improves signal-to-noise ratio. In terms of preparation process, the combination of H2 plasma pretreatment and atomic layer deposition realizes the atomic-level uniform distribution of doped atoms, overcomes the problem of uneven diffusion of traditional doping process, and ensures the consistency of material performance; The precise integration of self-aligned photolithography technology and conductive vias reduces the alignment error of the electrode and the temperature-sensitive layer, reduces the parasitic capacitance and improves the signal transmission efficiency. The arrayed electrode unit design of the sensor and the combination of the flexible packaging layer not only improve the spatial resolution, but also enhance the environmental adaptability and mechanical stability of the device. The overall scheme realizes the deep integration of material modification, structure innovation and process optimization, breaks through the limitations of existing two-dimensional material sensors in resolution, stability and integration accuracy, provides an efficient solution for accurate detection of multiple physical quantities in complex scenarios, and has significant application value and technical advantages in intelligent equipment, medical health and other fields.

[0049] The above are only preferred embodiments of the present application and the technical principles applied. The present application is not limited to the specific embodiments herein, and various obvious changes, readjustments and replacements that can be made by those skilled in the art will not deviate from the protection scope of the present application. Therefore, although the present application has been described in more detail through the above embodiments, the present application is not limited to the above embodiments, and can include more other equivalent embodiments without deviating from the concept of the present application, and the scope of the present application is determined by the scope of the claims.

Claims

1. A flexible substrate material doped with a two-dimensional material, characterized in that: include: A two-dimensional material substrate, wherein the two-dimensional material is at least one of graphene, molybdenum disulfide, tungsten diselenide or black phosphorus; a composite doping atomic layer, wherein the composite doping atoms include nitrogen and boron, the atomic doping ratio of nitrogen to boron is 1:3 to 3:1, and the composite doping atoms are uniformly distributed on the surface and grain boundary defects of the two-dimensional material substrate; The insulating isolation layer is a boron nitride nanosheet and / or an aluminum oxide film, which covers the surface of the two-dimensional material substrate and has a thickness of 5-20 nm.

2. The electrode material according to claim 1, characterized in that The two-dimensional material substrate is a heterojunction formed by graphene and MoS2, the thickness of the graphene layer in the heterojunction is 1-3 atomic layers, the thickness of the MoS2 layer is 2-5 atomic layers, and the composite doping atoms are preferentially enriched in the edge active sites of the MoS2 layer.

3. The electrode material according to claim 1, characterized in that The total doping concentration of the composite doping atoms is 1×10 13 cm -2 to 5×10 14 cm -2 The surface work function of the two-dimensional material substrate is 4.2-5.1eV, which can be continuously adjusted by adjusting the doping ratio of nitrogen and boron.

4. A method for preparing a high-resolution array sensor based on the electrode material according to any one of claims 1 to 3, characterized in that: The following steps are involved: Pretreatment of 2D material flexible substrates: Transfer the 2D material film onto a silicon and / or polyimide substrate and treat with H2 plasma using the following parameters: H2 flow rate 60-120 mL / min, RF power 1.4-1.8 A. NH3 and B2H6 gases are introduced sequentially with a flow ratio of 1:1 to 3:1, and atomic layer deposition is performed at 200-400°C with a deposition cycle of 50-200 times; forming a nanosheet layer and / or an Al2O3 film on the surface of the doped two-dimensional material by spin coating and / or chemical vapor deposition, wherein the thickness is controlled to be 5-20 nm by the deposition time; Self-aligned lithography technology is used to define arrayed electrode patterns on the surface of flexible substrate materials with a line width of ≤10μm. A vanadium oxide temperature-sensitive layer with a thickness of 100-300nm is deposited by electron beam evaporation and connected to the signal processing ASIC chip through conductive through-holes with a diameter of ≤5μm.

5. The preparation method according to claim 4, characterized in that In the steps, the purity of NH3 gas is ≥99.999%, the partial pressure of B2H6 gas is controlled to be 1-5Pa, and the substrate temperature fluctuation during the deposition process is ≤±5°C.

6. The preparation method according to claim 4, characterized in that When the two-dimensional material substrate is a graphene / MoS2 heterojunction, H2 plasma treatment forms sulfur vacancy defects on the surface of the MoS2 layer with a defect density of 1×10 12 cm -2 ~5×10 12 cm -2 .

7. The preparation method according to claim 4, characterized in that The overlay accuracy of the self-aligned lithography technology is ≤2μm. It uses a deep ultraviolet lithography light source with a wavelength of 248nm. The edge alignment error between the electrode and the temperature-sensitive layer is ≤1μm.

8. The preparation method according to claim 4, characterized in that The signal processing ASIC chip integrates a low-noise amplifier and a 24-bit A / D converter. The conductive through hole has a depth-to-width ratio of 5:1 to 10:1 and is filled with a filler.

9. The preparation method according to claim 4, characterized in that It also includes the steps of constructing a gradient doped heterostructure: between the two-dimensional material substrate and the insulating isolation layer, by segmentedly controlling the ALD gas flow rate, an N doping concentration gradient of 10%-90% and a B doping concentration gradient of 90%-10% are formed, and the energy band offset ΔE of the gradient heterojunction is 0.3-0.8eV.

10. The preparation method according to claim 4, characterized in that The arrayed electrode units of the sensor are distributed in an m×n matrix, where m and n are ≥ 2. The size of a single electrode unit is 20μm×20μm to 50μm×50μm, the unit spacing is 50μm to 100μm, and adjacent electrode units are isolated by a silicon dioxide insulating layer with a thickness of 1-5μm.

Citation Information

Patent Citations

  • Miniature piezoresistive type stress sensor based on tungsten diselenide

    CN109297622A

  • Hexagonal boron nitride / titanium dioxide heterojunction-based doped material and preparation method thereof

    CN119897144A

  • Engineering carbon-based structures for sensing applications

    US20210131994A1

Cited By

  • Skin-friendly antibacterial ammonia-inhibiting paper diaper surface layer, preparation method thereof and paper diaper

    CN122272863A